The Video Head Impulse Test to Assess the Efficacy of Vestibular Implants in Humans - Guinand, Nils; Van de Berg, Raymond; Cavuscens, Samuel; Ranieri, Maurizio; Schneider, Erich; Lucieer, Floor; Kingma, Herman; Guyot, Jean-Philippe; Pérez Fornos, Angélica (Frontiers in Neurology, 2017)
The purpose of this study was to evaluate whether it is possible to restore the high-frequency angular vestibulo-ocular reflex (aVOR) in patients suffering from a severe bilateral vestibulopathy (BV) and implanted with a vestibular implant prototype. Three patients (S1-3) participated in the study. They received a prototype vestibular implant with 1-3 electrode branches implanted in the proximity of the ampullary branches of the vestibular nerve. Five electrodes were available for electrical stimulation: one implanted in proximity of the left posterior ampullary nerve in S1, one in the left lateral and another one in the superior ampullary nerves in S2, and one in the right lateral and another one in the superior ampullary nerves in S3. The high-frequency aVOR was assessed using the video head impulse test (vHIT; EyeSeeCam; EyeSeeTec, Munich, Germany) while motion-modulated electrical stimulation was delivered via one of the implanted vestibular electrodes at a time. aVOR gains were compared to control measurements obtained in the same patients when the device was not activated. In 3 out of the 5 tested electrodes the aVOR gain increased monotonically with increased stimulation strength when head impulses were delivered in the plane of the implanted canal. In these cases gains ranging from 0.4 to values above 1 were measured. A “reversed” aVOR could also be generated when inversed stimulation paradigms were used. In most cases, the gain for excitatory head impulses was superior to that recorded for inhibitory head impulses, consistent with unilateral vestibular stimulation. Improvements of aVOR gain were generally accompanied by a concomitant decrease of corrective saccades, providing additional evidence of an effective aVOR. High inter-electrode and inter-subject variability were observed. These results, together with previous research, demonstrate that it is possible to restore the aVOR in a broad frequency range using motion-modulated electrical stimulation of the vestibular afferents. This provides additional encouraging evidence of the possibility of achieving a useful rehabilitation alternative for patients with BV in the near future.